Developing a system that uses ultrawide-band inertial measurement units to quantify selected 10-Pin skills in real-time - Wee, Joel Jiewei (Nanyang Technological University, 2022)
Ten-pin bowling is a unique abstract sport that requires bowlers to deliver a 11-to-16-pound ball in a five-step approach for the ball to travel down the oiled lane to knock down 10 pins. This can be achieved through consistency in timing of the approach, accuracy of movement and reliance on equipment such as a bowling ball. At a competitive level, there is a need for professional training and a need for improved training methods. With competitive sports around, there have been many research that has been conducted to change and work on athletes’ technique and training methods with one of it being wearable sensor technology. The current method in assessing ten-pin bowling movements is using the 3D motion capture system, the gold standard in movement analysis. While 3D motion capture systems allow the collection of highly accurate data, setting up the system on the training ground is laborious and although it is possible, logistically it is not always easy as the set-up is laborious and time consuming thus testing sessions are mainly conducted in a laboratory environment. With the emergence of wearable sensor technology presents the opportunity for 3D movements to be captured in-situ and with less setup time involved. However, there has been little research on wearable sensor technology and its applications in ten-pin bowling. The objectives of this research project are to develop a system that uses wearable sensors to identify bowling specific movements in real time. The data will allow coaches and athletes to monitor the athletes’ training performance and plan a more targeted training program based on the shortcomings revealed from the data collected with the aim of enhancing the athlete’s performance. This project would utilised a customised relative orientation sensor consisting of a three-axis accelerometer and a three-axis gyroscope. The sensor is small and lightweight which allows for data collection without restricting the bowler’s movement. A graphical user interface was developed to provide a training summary which displays the distance between each step and the timing of each step along with the step phases to provide feedback on the bowler’s movement. These variables were chosen as in bowling, the timing of each step and how far each step the bowler takes plays an important role in the execution of a bowling shot. The changes in the variables would affect the bowler’s timing of the ball swing, causing the ball to be released inaccurately onto the bowling lane.